2022
DOI: 10.22581/muet1982.2201.14
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling and Rehabilitation of Irrigation Outlets in Water Distribution of Canals in Punjab, Pakistan

Abstract: This paper highlights the problems associated with the outlets in the irrigation system of Pakistan, leading to the design of outlets, to trace the gradual evolution of various outlets types and to describe most of the types that have been evolved so far. The advantages and limitations of each type have been examined critically so that the selection of a type for any particular set of conditions may be rendered easy. An outlet is a flow measuring and controlling device between farmer’s land and an irrigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been concluded that improperly designed outlets can cause several issues, including variations in discharge coefficients, inequitable water distribution, canal siltation, inadequate water availability at lower outlets, lack of incentives for water conservation, and insufficient drainage. Faulty outlets are also a major contributing factor to canal siltation [104].…”
Section: Performance Of Different Canal Sectionsmentioning
confidence: 99%
“…It has been concluded that improperly designed outlets can cause several issues, including variations in discharge coefficients, inequitable water distribution, canal siltation, inadequate water availability at lower outlets, lack of incentives for water conservation, and insufficient drainage. Faulty outlets are also a major contributing factor to canal siltation [104].…”
Section: Performance Of Different Canal Sectionsmentioning
confidence: 99%